Islamic Ethical Pedagogy for Bullying Prevention: Integrating Gender Education in Digital Learning Communities - Rizky Maulana Firmansyah; A. Faizul Mubarak (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
Despite the growing implementation of anti-bullying programs in schools, existing approaches frequently remain behaviorally oriented and insufficiently address the structural dimensions of gender inequality, symbolic violence, and ethical awareness within educational environments. This study aims to examine bullying prevention through the integration of gender education within Islamic Religious Education (Pendidikan Agama Islam/PAI) grounded in Islamic ethical values and implemented through digital learning communities. Employing a qualitative case study design, this research was conducted within the Eudaimonia digital community in Probolinggo, Indonesia. Data were collected through participant observation, semi-structured interviews, and documentation studies, and analyzed using thematic analysis. The findings reveal that bullying operates as a form of symbolic violence reproduced through hegemonic gender constructions and unequal social relations among students. The integration of Islamic ethical values, including musāwah (equality), ‘adl (justice), raḥmah (compassion), and karāmah insāniyyah (human dignity), contributed significantly to the development of students’ critical awareness, empathy, and prosocial behavior. Furthermore, the Eudaimonia digital community functioned as a transformative pedagogical space facilitating reflective dialogue, collaborative learning, and continuous ethical internalization. This study proposes an integrative framework conceptualized as Islamic Ethical Digital Pedagogy, which combines Islamic ethical traditions, gender-responsive education, and participatory digital learning within a holistic anti-bullying strategy. The study contributes theoretically to contemporary Islamic education discourse by repositioning digital learning communities as critical-transformative pedagogical spaces for fostering inclusive, just, and anti-violent educational cultures in the digital era.